Knowledge Diffusion through Employee Mobility - April Mitchell Franco; Darren Filson (Claremont McKenna College, Department of Economics, 2000)
In high-tech industries, one important method of diffusion is through employee mobility: many of the entering firms are started by employees from incumbent firms using some of their former employers' technological know-how. This paper explores the effect of incorporating this mechanism in a general industry framework by allowing employees to imitate their employers' know-how. The equilibrium is Pareto optimal since the employees 'pay' for the possibility of learning their employers' know-how. The model's implications are consistent with data from the rigid disk drive industry. These implications concern the effects of know-how on firm formation and survival.
Keywords: P16; E62; O40; 330; socio-political instability; endogenous growth; public investment; political economy of growth